The Impact of Perceived Value on Consumers’ Positive Word-of-mouth Intention Toward Energy-efficient Appliances - Le, Bao Ngoc; Nguyen , Nguyet (International Journal of Energy Economics and Policy, 2024)
This study examines the dimensions of consumer perceived value that contribute to customer satisfaction and lead to positive word-of-mouth intention regarding energy-efficient appliances. An online questionnaire was administered to 351 consumers of energy-efficient appliances in Vietnam. Structural equation modeling results reveal that three consumer perceived values (functional value, environmental value, and emotional value) have a positive impact on customer satisfaction, which in turn enhances consumers’ positive word-of-mouth intention. Moreover, this study revealed that the relationship between emotional value and customer satisfaction, as well as the relationship between environmental value and customer satisfaction, differs significantly between individuals with higher education levels and low education levels. The research findings contribute to the existing knowledge on pro-environmental behavior and relationship marketing. They also provide significant insights for policymakers, manufacturers and retailers in the energy-efficient appliances sector to encourage consumers to recommend energy-efficient products.